Penerapan Semantik Sebagai Strategi Pembentuk Elemen Desain Berdasarkan Tipologi Rupa Wayang Purwa Pandawa - Prabawa, Fialin Aryastri; Dewi, Pancawati (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2022)
The use of shadow puppets as an object in the formation of an architectural design has been widely used. This is due to the elements of meaning and description and the philosophy closely related to Javanese society. Of the several case studies that have been found, most still focus on the form of shadow puppet and have not focused on the use of meaning as the main focus, so further studies are needed on the use of the appearance and meaning of shadow puppet in architectural forms. Qualitative methods are used by performing typology and semantic processes based on the Gestalt similarity principle to form meaning and rereading new meanings into form to form design elements. The results showed that the Pandava shadow puppets can be used as an object that allows it to use in forming architectural design elements based on visual typology and semantics of meaning.